GABA Signaling in Spatial Memory changes in Animal Model of Alzheimer’s disease - Bahareh Tavakoli-Far; Marjan Hosseini; Hadi Goudarzvand; Samira Choopani; Mahdi Goudarzvand (نشریه دانشگاه علوم پزشکی البرز)
Introduction: Alzheimer's disease is a progressive disease with mild memory loss that eventually leads to the loss of the ability to conduct conversation and react to the environment. Despite the proven role of the drugs used against the obvious causes of Alzheimer's disease, it still seems impossible to achieve an effective and permanent treatment for the treatment of Alzheimer's disease. So, investigating different angles of GABAergic system signaling can be introduced as a promising target for the development of anti-Alzheimer drugs. Materials and Methods: To induce Alzheimer's disease, the β-amyloid toxin at a dose of 5µg/µl was injected bilaterally into the hippocampus of Wistar male rats, and the rats were then treated with bilateral injection of GABA-A receptor agonist (muscimol) and antagonist (bicuculline), at a dose of 100 ng/µl/side in the hippocampus for 4 days. To assess the spatial memory of the animals, the parameters of the distance traveled by the animals, latency time to reach the hidden platform, and velocity of the animals were analyzed in Morris water maze test.